2019
DOI: 10.3390/su11061739
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Urban Expansion and Socioeconomic Vitality Using NPP-VIIRS Data in Xia-Zhang-Quan, China

Abstract: Studying the spatiotemporal evolution of urban expansion in the Xia-Zhang-Quan metropolitan area (XZQ) is of crucial importance, to effectively guide coordinated development and industrial adjustment during urbanization. Based on National Polar Partnership-Visible Infrared Imaging Radiometer Suite (NPP-VIIRS) data this study used an analytical method of irregular spatial grids to explore and evaluate the dynamics of urban spatial expansion and urban socioeconomic vitality in XZQ between 2013 and 2017. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 52 publications
3
7
0
Order By: Relevance
“…After further decomposition, it is found that the inequality gap between two cities is decreasing, while the inequality gap within one city is increasing, which is consistent with the research results of Jiang et al [18]. Jiang et al pointed out that with the improvement of the coordination and integration degree of regional infrastructure construction, the integration trend of Xiamen, Zhangzhou, and Quanzhou was more obvious from 2013 to 2018 [18]. From the perspective of urban space, the three cities in the abovementioned study are distributed in a contiguous area, the urban cluster is densely populated with cities, the boundaries between cities are increasingly blurred, and the urban development…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…After further decomposition, it is found that the inequality gap between two cities is decreasing, while the inequality gap within one city is increasing, which is consistent with the research results of Jiang et al [18]. Jiang et al pointed out that with the improvement of the coordination and integration degree of regional infrastructure construction, the integration trend of Xiamen, Zhangzhou, and Quanzhou was more obvious from 2013 to 2018 [18]. From the perspective of urban space, the three cities in the abovementioned study are distributed in a contiguous area, the urban cluster is densely populated with cities, the boundaries between cities are increasingly blurred, and the urban development…”
Section: Discussionsupporting
confidence: 90%
“…The regression analysis shows that the Theil index of the two is weakly correlated, and the measurement coefficient is R 2 =0.563. After further decomposition, it is found that the inequality gap between two cities is decreasing, while the inequality gap within one city is increasing, which is consistent with the research results of Jiang et al [18]. Jiang et al pointed out that with the improvement of the coordination and integration degree of regional infrastructure construction, the integration trend of Xiamen, Zhangzhou, and Quanzhou was more obvious from 2013 to 2018 [18].…”
Section: Discussionsupporting
confidence: 83%
“…The urbanization process in China's coastal zone is significantly affected by resource distribution and the impacts of national and regional development policies [39,40]. A number of studies have been carried out to monitor the spatiotemporal characters of urban land in China's coastal zone [24,39,[41][42][43][44]. Most of these have attached importance to large and developed cities, such as Guangzhou [24], and urban agglomerations [23,39].…”
Section: Introductionmentioning
confidence: 99%
“…Night time light (NTL) uses sensors to record nighttime lights on the surface [ 36 , 37 ], which is a crucial approximation of economic and social development and human activity [ 38 ]. Among them, the Defense Meteorological Satellite Program’s Operational Linescan System (DMSP/OLS) data have been widely used since the 1990s [ 39 ]. In 2011, Suomi-NPP Visible Infrared Imaging Radiometer Suite (NPP/VIIRS) was used to obtain a new generation of nighttime light data [ 40 ].…”
Section: Introductionmentioning
confidence: 99%